Stability-indicating liquid chromatographic method for the determination of Letrozole in pharmaceutical formulations - M. Mathrusri Annapurna; Chitaranjan Mohapatro; A. Narendra (Elsevier, 2012)
A stability-indicating high-performance liquid chromatographic method was developed and validated for the determination of Letrozole in tablet dosage forms. Reversed-phase chromatography was performed on Shimadzu Model LC-Class-Vp with Lichrocart/Lichrosphere 100 C-18 (250Â mmÃ4.6Â mm, 5Â Î¼m particle size) column with methanol: tetra butyl ammonium hydrogen sulfate (80:20V/V) as mobile phase at a flow rate of 1Â mL/min with UV detection at 240Â nm. Linearity was observed in the concentration range of 0.5â150Â Î¼g/mL (R2=0.9998) with regression equation y=102582x+43185. The limit of quantitation (LOQ) and limit of detection (LOD) were found to be 0.043 and 0.012Â Î¼g/mL respectively. The forced degradation studies were performed by using HCl, NaOH, H2O2, thermal and UV radiation. Letrozole is more sensitive towards alkaline conditions and very much resistant towards acidic, oxidative and photolytic degradations. The method was validated as per ICH guidelines. The RSD for intra-day (0.78â0.97) and inter-day (0.86â0.96) precision were found to be lesser than 1%. The percentage recovery was in good agreement with the labeled amount in the pharmaceutical formulations and the method is simple, specific, precise and accurate for the determination of Letrozole in pharmaceutical formulations. Keywords: Letrozole, Liquid chromatography, Stability-indicating